2017
DOI: 10.3354/dao03162
|View full text |Cite
|
Sign up to set email alerts
|

Epizootiology of the ectoparasitic protozoans Ichthyobodo salmonis and Trichodina truttae on wild chum salmon Oncorhynchus keta

Abstract: Infestations of the ectoparasitic flagellate Ichthyobodo salmonis and the ciliate Trichodina truttae have caused acute mortalities of hatchery-reared juvenile chum salmon Oncorhynchus keta in Hokkaido, northern Japan. This study examined the epizootiology of I. salmonis and T. truttae on wild chum salmon as a possible infection source of the 2 parasitic protozoans in hatcheries. Infestations by both ectoparasites were detected on freshwater-adapted adult and juvenile chum salmon in all 4 rivers examined. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…For artificial transmission from infected to uninfected animals by means of cohabitation, it is generally considered that all groups are not subjected to the same pathogenic pressure, because the infected animals do not all have the same infection intensity; this condition may therefore influence the accuracy of the results. Even so, previous studies on artificial transmission of I. salmonis and T. truttae in O. keta juveniles suggested that transmission through cohabitation of ≥20 infected fish and ≥500 uninfected fish could ensure relatively consistent experimental results (Mizuno et al ., , , ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For artificial transmission from infected to uninfected animals by means of cohabitation, it is generally considered that all groups are not subjected to the same pathogenic pressure, because the infected animals do not all have the same infection intensity; this condition may therefore influence the accuracy of the results. Even so, previous studies on artificial transmission of I. salmonis and T. truttae in O. keta juveniles suggested that transmission through cohabitation of ≥20 infected fish and ≥500 uninfected fish could ensure relatively consistent experimental results (Mizuno et al ., , , ).…”
Section: Methodsmentioning
confidence: 99%
“…These considerations suggest that the oregano-supplemented juveniles released from the hatchery could reach the ocean without heavy mortalities due to T. truttae infection. In addition, the oregano-supplemented juveniles would survive in the ocean, regardless of an episode of T. truttae infection in the river, since the protozoan cannot survive in seawater (Khan, 1991;Mizuno et al, 2017b). Consequently, T. truttae infection among oregano-supplemented juveniles (such as in experiment 2) would not pose a serious problem for O. keta stock enhancement programmes.…”
Section: Feasibility Of Preventive Treatment Against the Two Protozmentioning
confidence: 99%
See 1 more Smart Citation
“…All sampled fish were examined for infection with either I. salmonis or T. truttae in accordance with a previously established method (Mizuno, Urawa, Miyamoto, Saneyoshi et al, 2017). In brief, to detach ectoparasitic protozoans from the skin of the fish, juveniles were individually anaesthetized in 1 g/L unbuffered tricaine methanesulfonate (MS-222; Callahan & Noga, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…In Hokkaido salmon hatcheries, the infection sources of I. salmonis and T. truttae are considered to be wild chum salmon and various other wild salmonids, respectively (Mizuno, Urawa, Miyamoto, Saneyoshi et al., ). Once separated from a host fish, each of these parasites can easily invade hatchery ponds via the river water used for aquaculture.…”
Section: Introductionmentioning
confidence: 99%